2015
DOI: 10.1111/cmi.12522
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of mesenchymal stem cells against Escherichia coli is mediated by secretion of beta‐ defensin‐ 2 via toll‐ like receptor 4 signalling

Abstract: SummaryRecently, we demonstrated that intratracheal transplantation of human umbilical cord blood‐ derived mesenchymal stem cells (MSCs) attenuates Escherichia (E) coli‐ induced acute lung injury primarily by down‐ modulating inflammation and enhancing bacterial clearance iQn mice. This study was performed to elucidate the mechanism underlying the antibacterial effects of MSCs. The growth of E. coli in vitro was significantly inhibited only by MSCs or their conditioned medium with bacterial preconditioning, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
160
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(170 citation statements)
references
References 36 publications
9
160
0
1
Order By: Relevance
“…On the other hand, current data suggest that MSCs exert strong antimicrobial effects through indirect and direct mechanisms (1626). Indirectly, across their role in the host immune response against pathogens, especially in the dynamic coordination of the pro- and anti-inflammatory elements of the immune system (22, 2729) or increasing the activity of phagocytes (18, 21, 25, 30, 31); and directly, by the secretion of antimicrobial peptides and proteins (AMPs) (19, 20, 23, 24, 26), and also by the expression of molecules such as indoleamine 2,3-dioxygenase (IDO) (16) and interleukin (IL)-17 (32). In fact, MSCs have been reportedly responsible of the bacterial clearance in preclinical models of sepsis (1720, 22, 25), acute respiratory distress syndrome (ARDS) (21, 26), and cystic fibrosis infection (23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, current data suggest that MSCs exert strong antimicrobial effects through indirect and direct mechanisms (1626). Indirectly, across their role in the host immune response against pathogens, especially in the dynamic coordination of the pro- and anti-inflammatory elements of the immune system (22, 2729) or increasing the activity of phagocytes (18, 21, 25, 30, 31); and directly, by the secretion of antimicrobial peptides and proteins (AMPs) (19, 20, 23, 24, 26), and also by the expression of molecules such as indoleamine 2,3-dioxygenase (IDO) (16) and interleukin (IL)-17 (32). In fact, MSCs have been reportedly responsible of the bacterial clearance in preclinical models of sepsis (1720, 22, 25), acute respiratory distress syndrome (ARDS) (21, 26), and cystic fibrosis infection (23).…”
Section: Introductionmentioning
confidence: 99%
“…These molecules have selective activity against a wide range of organisms including bacteria, yeasts, fungi, viruses, and even cancer cells (34). So far, MSCs have been found to constitutively express four AMPs: cathelicidin LL-37 (19, 23), human β-defensin-2 (hBD-2) (24), hepcidin (20), and lipocalin-2 (Lcn2) (26), which can be further modulated during infection and inflammation. In fact, it has been demonstrated that, in MSCs, a bacterial preconditioning induces an upregulation of LL-37, hBD-2, and hepcidin (19, 20, 24), while their preconditioning with inflammatory stimuli evoke increasing levels of LL-37 and Lcn2 (23, 26).…”
Section: Introductionmentioning
confidence: 99%
“…Th e hBD-2 obtained during intratracheal transplantation of human umbilical cord blood-derived mesenchymal stem cells in the experimental mouse model has been shown to primarily down-modulate infl ammation and enhance bacterial clearance in Escherichia coli-induced acute lung injury [32]. Another study suggests that the Wharton's jelly-derived mesenchymal stem cells having a low immunogenicity and immunomodulatory eff ect might be related to direct cell contact and the inhibition of cytokine secretion by human peripheral blood lymphocytes [36].…”
Section: Discussionmentioning
confidence: 99%
“…Existen pocos trabajos en la literatura que reporten el uso de parámetros cinéticos para determinar la susceptibilidad de bacterias patógenas a la presencia de péptidos antimicrobianos usando modelos matemáticos y muchos de ellos son solamente descriptivos tales como los reportados por Steinberg et al, (1997); Harman et al, (2017);Fanter et al, (2010); Freire et al, (2015); Bolintineau et al, (2010); Sung et al, (2016). Esto es debido a que posiblemente, los AMPs, en muchos casos, son todavía una promesa terapéutica para reemplazar a los antibióticos, por lo tanto, existen pocos estudios clínicos sistemáticos.…”
Section: Discusionunclassified